The left and right hands of the Portuguese state: Welfare retrenchment of public employment - Mauritti, R; Nunes, N.; Botelho, M.C.; Craveiro, D. (Portuguese Journal of Social Science, 2020)
This article focuses on welfare retrenchment in Portugal by analysing the evolution of public sector employment up until 2013. A multidimensional analysis of the structure of public employment in the Portuguese state was developed, theoretically guided by the ‘hands of the state’ model proposed by Bourdieu, which divides the main functions of contemporary states between its left hand (more redistributive) and its right hand (more rational economic-oriented). Bourdieu’s approach is especially useful in addressing the transformations of the Portuguese public employment between 1979 and 2013, characterized by specific economic, social and political changes. In 2013 – a year in which the adjustment measures agreed by the Portuguese government, the European Central Bank, the European Commission and the International Monetary Fund during the global crisis were especially intense – we observed the tendency towards the disqualification of public employment and the shrinking of the left hand of the Portuguese state. Public policy orientations in the areas of education and science were particularly troubling, considering the structural backwardness the country faces in these fields in the context of the European Union.